Evolution of Sweet Potato (Ipomoea batatas [L.] Lam.) Breeding in Cuba - Morales, A.; Ma, P.; Jia, Z.; Rodríguez, D.; Pastrana Vargas, I.J.; Ventura, V.; González, J.E.; Portal, O.; Diaz, F.; Parrado Alvarez, O.; Cordero, C.; Bian, X. (2025)
This study analyzed the genetic progress of sweet potato (Ipomoea batatas) breeding in Cuba over the past 50 years by field trials comparing traditional and improved varieties. Improved varieties significantly outperformed traditional ones in tuberous root yield, with an accumulated genetic gain of 0.20–0.37 t ha−1 per year, translating to a 256% yield increase. Improved genotypes also exhibited enhanced pest tolerance: lower weevil (Cylas formicarius) infestation and reduced nematode (Meloidogyne incognita) reproduction rates. For viral diseases, 60% of improved varieties showed incidence rates below 10%, compared with 90% of traditional varieties exceeding this threshold. Under drought conditions, improved varieties showed tolerance, with Stress Susceptibility Indices (SSIs) of less than 0.8, while the traditional varieties were more susceptible (SSI > 1). Phenotypic stability analysis via GGE biplot confirmed the superior yield and adaptability of improved varieties across environments. These advances underscore the critical role of sweet potatoes breeding in Cuba, with improvements in yield, quality and resistance to biotic and abiotic stress, contributing to strengthening climate resilience and food security.